Human airway epithelial extracellular vesicle miRNA signature is altered upon asthma development. Issue 2 (2nd October 2019) - Bartel, Sabine; La Grutta, Stefania; Cilluffo, Giovanna; Perconti, Giovanni; Bongiovanni, Antonella; Giallongo, Agata; Behrends, Jochen; Kruppa, Jochen; Hermann, Stefanie; Chiang, Dapi; Pfaffl, Michael W.; Krauss‐Etschmann, Susanne
Abstract: Background: miRNAs are master regulators of signaling pathways critically involved in asthma and are transferred between cells in extracellular vesicles (EV). We aimed to investigate whether the miRNA content of EV secreted by primary normal human bronchial epithelial cells (NHBE) is altered upon asthma development. Methods: NHBE cells were cultured at air‐liquid interface and treated with interleukin (IL)‐13 to induce an asthma‐like phenotype. EV isolations by precipitation from basal culture medium or apical surface wash were characterized by nanoparticle tracking analysis, transmission electron microscopy, and Western blot, and EV‐associated miRNAs were identified by a RT‐qPCR‐based profiling. Significant candidates were confirmed in EVs isolated by size‐exclusion chromatography from nasal lavages of children with mild‐to‐moderate (n = 8) or severe asthma (n = 9), and healthy controls (n = 9). Results: NHBE cells secrete EVs to the apical and basal side. 47 miRNAs were expressed in EVs and 16 thereof were significantly altered in basal EV upon IL‐13 treatment. Expression of miRNAs could be confirmed in EVs from human nasal lavages. Of note, levels of miR‐92b, miR‐210, and miR‐34a significantly correlated with lung function parameters in children (FEV1 FVC%pred and FEF25‐75%pred ), thus lower sEV‐miRNA levels in nasal lavages associated with airway obstruction. Subsequent ingenuity pathway analysis predicted the miRNAs to regulate Th2 polarization and dendritic cell maturation. Conclusion: Our data indicate that secretion of miRNAs in EVs from the airway epithelium, in particular miR‐34a, miR‐92b, and miR‐210, might be involved in the early development of a Th2 response in the airways and asthma. Abstract : Primary human bronchial epithelial cells secrete microRNA‐containing extracellular vesicles (EV) apically and basally. Upon Interleukin‐13‐induced goblet cell metaplasia, miR‐34a, miR‐92b, and miR‐210 levels in EVs are lower, which is predicted to influence dendritic cell maturation and Th2 polarization. Lower levels of these microRNAs in EVs in nasal lavages correlate with increased airway obstruction in children.